Exploring Out-of-Pocket Costs and Health-Related Quality of Life among Patients with Cancer and Diabetes in Malaysia - Dzulkipli, Mohd Redhuan; Shafie, Asrul Akmal; Maon, Siti Noorsuriani; Ramli, Azuana; Mohammad Yahaya, Abdul Haniff; Ho, See Wan; Muhsin, Nor Ilham Ainaa; Ahmat, Azmi Nor Mohd Farez (Malaysian Journal of Medical Sciences, 2025)
Background: Out-of-pocket costs for chronic illnesses have become significant barriers to continuing treatment, given the already substantial cost of the diseases. This study aims to estimate out-of-pocket costs and determine the health-related quality of life of patients with cancer and diabetes. Methods: A purposive cross-sectional study (January 2021–January 2022) was conducted to assess health-related quality of life and out-of-pocket costs among Malaysian adults with cancer or diabetes. Using the validated EQ-5D-5L and a three-section questionnaire, 571 participants from three hospitals and online surveys provided data on five cost categories expressed in 2021 MYR and USD. Results: Significant differences were observed across all cost categories between patients with cancer and diabetes. Diagnostic imaging had a larger effect size (P < 0.0001, r = 0.467). Annual outpatient and hospitalisation costs among patients with cancer were found to be 42 and 11 times higher than for patients with diabetes, respectively. Overall, the out-of-pocket expenditure per year for patients with cancer was MYR 88,346.12 and MYR 9,010.60 for patients with diabetes. Additionally, patients with cancer rated their health-related quality of life using the EQ-VAS score lower than patients with diabetes (EQ-VAS = 63.7, SD = 19.2 and EQ-VAS = 71.6, SD = 18.7). Conclusion: Cancer and diabetes impose significant financial and quality of life burdens on patients in Malaysia. This study highlights gaps in insurance coverage and public assistance, calling for more comprehensive support for medical and nonmedical expenses and psychological support for patients. The analysis, which focuses on annual costs, may underestimate the long-term financial impact, especially for patients with cancer. Future research should examine household spending and the ability to pay for treatment costs to better understand the full economic burden of these chronic diseases.